MENAKAR UNSUR GHARAR DAN MAYSIR DALAM INVESTASI ASET DIGITAL: STUDI HUKUM EKONOMI SYARIAH TERHADAP KRIPTO FAN NFT - Rosana, Mayang (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2026)
The advancement of digital technology has introduced new financial instruments such as cryptocurrencies and Non-Fungible Tokens (NFTs), which present both investment opportunities and challenges in the context of Islamic legal and ethical frameworks. From the perspective of Islamic economic law, every financial transaction must be free from uncertainty (gharar), speculation (maysir), and usury (riba) to ensure justice and public welfare. This study aims to examine the presence of gharar and maysir elements in digital asset investments and to analyze their compatibility with Islamic economic law and national regulations. The research employs a qualitative descriptive method through a literature review, analyzing scholarly works, the DSN-MUI Fatwa No. 140/DSN-MUI/IX/2021, and relevant legal frameworks such as the Electronic Information and Transactions Law (UU ITE), OJK Fintech regulations, and Bappebti policies. The findings reveal that cryptocurrencies and NFTs may involve gharar due to unclear value and absence of tangible underlying assets, and maysir through speculative trading behaviors resembling digital gambling. Nevertheless, digital asset transactions may be deemed permissible if they ensure transparency, clear utility, and freedom from manipulation and excessive speculation. The harmonization between Islamic economic principles and national law is crucial to ensure legal certainty, consumer protection, and ethical digital investment practices. This study recommends strengthening Islamic financial literacy and regulatory collaboration to build a fair and sharia-compliant digital economy aligned with the objectives of maqasidh al-syariah. Keywords: Digital assets, Gharar and Maysir, Cryptocurrency, NFT, Islamic economic law